Avaliação da atividade angiogênica e do potencial de cicatrização do látex de euphorbia tirucalli (AVELOZ) - Bessa, Guilherme de Oliveira (2010)
Through this research we aim to demonstrate the effectiveness of the latex of E. tirucalli in wound care as an adjunct in the healing process. The latex was obtained from a specimen plant in the city of Goiania, and diluted to the concentration of 1mg/mL. Two experiments were conducted using experimental models: the chorioallantoic membrane of embryonated chicken eggs and wounds in rats. In the first experiment, we evaluated the angiogenic response of the use of latex membranes, compared with controls. In the second one, sequential measurements were made of the wounds of rats, with regular use of the substance and controls until complete healing of the lesions. The results showed effective healing and angiogenic stimuli, similar to the positive control used (the latex of rubber tree).